Neuromuscular Disorders in Children and Adolescents - Korinthenberg, Rudolf (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Significant scientific and therapeutic advances have been made in recent decades, particularly in hereditary but also in acquired neuromuscular diseases. As a result of our increasing etiological understanding, the classification of these diseases has changed from a clinical-descriptive and formal-genetic to a molecular-genetic and pathophysiological one. This has led to an intensification of research into the diagnosis and treatment of these diseases, resulting in the first effective gene-modifying treatments for DMD and SMA in recent years and, more recently, gene replacement therapy for the most severe form of SMA. In addition, great strides have been made in symptomatic and rehabilitative treatment, making it possible to improve the functioning and quality of life of those affected and their families. This Special Issue of Children contains a collection of 12 studies and reviews dealing with genetic and acquired peripheral nerve and muscle disorders.